Fear, loss and meaningful play: Permadeath in DayZ. Issue 2 (1st June 2017) - Carter, Marcus; Allison, Fraser
This article interrogates player experiences with permadeath in the massively multiplayer online first-person shooter (MMOFPS) DayZ. We analyse the differences between 'good' and 'bad' instances of permadeath and argue that meaningfulness – in accordance with Salen and Zimmerman's concept of meaningful play – is a critical requirement for positive experiences with permadeath. In doing so, this article suggests new ontologies for meaningfulness in play, and demonstrates how meaningfulness can be a useful lens through which to understand player experiences with negatively valenced play. We conclude by relating the appeal of permadeath to the excitation transfer effect, drawing parallels between the appeal of DayZ and fear-inducing horror games such as Silent Hill 2 and gratuitously violent and gory games such as Mortal Kombat.